Case report: subacute thyroiditis after receiving SARS-CoV-2 vaccine, maybe not only adjuvants - Huang, Yizhou; Chen, Xingyu; Wang, Qing; Lei, Xiaowei; Zhang, Lili (Frontiers in Medicine, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has induced the new coronavirus disease 2019 (COVID-19) pandemic worldwide, and SARS-CoV-2 vaccines are designed to control the transmission of the diseases. However, post-vaccination subacute thyroiditis (SAT) also appears with the increased vaccination rate. Three cases of SAT after SARS-CoV-2 vaccines are described in this study. We have reported the patients’ clinical symptoms, laboratory tests, and thyroid imaging. The tests for COVID-19 were all negative, and they did not report thyroid-related disease, autoimmune disease, or preceding upper respiratory system infection in their medical history. Three female patients all showed neck pain on physical examination. The laboratory test results and imaging findings were consistent with the diagnostic criteria of SAT. These patients were carried out standardized treatment according to their symptoms, and we closely followed up their response to the treatment. Clinicians must be aware of the possibility of SAT after receiving the vaccines and make timely therapy.